Violence against pregnant women in special police departments for assistance to women in Teresina-PI - Santos, Ariane Gomes dos; Nery, Inez Sampaio; Rodrigues, Danielle Carvalho; Melo, Ariel de Sousa (Rev Rene, 2010)
Violence against women is defined as any act or conduct based on gender, which causes death, injury or physical, sexual or psychological suffering. The objective of this research was to measure the phenomenon of domestic violence against pregnant women by recording such occurrence in Special Police Departments for Assistance to Women (DEAMs) in Teresina-PI in 2008. It is a quantitative research of retrospective and documentary analysis nature. A semi-structured questionnaire was used for data collection. The sample consisted of 71 Police reports of violent incidents against pregnant women in 2008 in two DEAMs of Teresina-PI. It was observed that 42,3% of them were housekeepers; 31,0% were between 22 and 26 years old; the main responsible for such violence acts were their partners (38,0%), husbands (18,3%) and ex-partners (18,3%); of the physical kind (32,5%), psychological (31,7%) and moral (30%) . It was concluded that the population of women who denounced their partners was small. It was probably because they are malleable to the fellow promises of no more beating.